Cost-effectiveness of ambulatory care management of primary spontaneous pneumothorax: an open-label, randomised controlled trial. Issue 9 (30th March 2022) - Luengo-Fernandez, Ramon; Landeiro, Filipa; Hallifax, Rob; Rahman, Najib M
Abstract : Background: Ambulatory management of primary spontaneous pneumothorax has been shown to reduce initial hospitalisation, but at the expense of increase adverse events. As a result, questions remain about the cost-effectiveness of this option. Objectives: A within-trial economic evaluation alongside a randomised controlled trial was performed to assess the cost-effectiveness of ambulatory care when compared with standard guideline-based management. Methods: Patients were randomly assigned to treatment with either an ambulatory device or standard guideline-based management (aspiration, standard chest tube insertion or both). Follow-up was 12 months. Outcomes included healthcare resource use and costs, quality of life, quality-adjusted life-years (QALYs) and cost-effectiveness. Results: 236 patients were recruited and randomly assigned to ambulatory care (n=117) and standard care (n=119). After multiple imputation for missing data, patients in the ambulatory care group had significantly lower National Health Service healthcare costs (−£788, 95% CI difference: −1527 to −50; p=0.037) than those in the standard care group. There were no differences in the number of QALYs gained (mean difference: −0.001, 95% CI difference: −0.032 to 0.030; p=0.95). When standard care was compared with ambulatory care, the incremental cost-effectiveness ratio was £799 066 per QALY gained, well above current thresholds of cost-effectiveness. As a result, the probability of ambulatory care being cost-effective was 0.93. Conclusion: Outpatient ambulatory management is highly likely to be a cost-effective option in the management of primary pneumothorax. Trial registration number: ISRCTN79151659 .